Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1159/000151743
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Tissue Engineering Using Subcultured Enamel Organ Epithelial Cells in Combination with Dental Pulp Cells

Abstract: We describe a strategy for the in vitro engineering of enamel tissue using a novel technique for culturing enamel organ epithelial (EOE) cells isolated from the enamel organ using 3T3-J2 cells as a feeder layer. These subcultured EOE cells retain the capacity to produce enamel structures over a period of extended culture. In brief, enamel organs from 6-month-old porcine third molars were dissociated into single cells and subcultured on 3T3-J2 feeder cell layers. These subcultured EOE cells were then seeded ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…We have previously shown that dental epithelial cells have the potential to induce chondrocytes from mesenchymal cells (14,15). The extracellular matrix in the regenerated cartilage was strongly stained with alcian blue (14,15,56). To exclude the possibility of cell contamination, we confirmed that only human-origin cells were stained positive for anti-human nuclei antibody, while ratand porcine-origin cells were not stained.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We have previously shown that dental epithelial cells have the potential to induce chondrocytes from mesenchymal cells (14,15). The extracellular matrix in the regenerated cartilage was strongly stained with alcian blue (14,15,56). To exclude the possibility of cell contamination, we confirmed that only human-origin cells were stained positive for anti-human nuclei antibody, while ratand porcine-origin cells were not stained.…”
Section: Discussionsupporting
confidence: 57%
“…To assess chondrogenic differentiation potential, the migrated cells were combined with dental epithelium and implanted into the omenta of immunodeficient rats. We have previously shown that dental epithelial cells have the potential to induce chondrocytes from mesenchymal cells (14,15). The extracellular matrix in the regenerated cartilage was strongly stained with alcian blue (14,15,56).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The first one consists in the engineering of dental constituents, such as the periodontium, the pulp/dentin, or the enamel/dentin complexes (Duan et al, 2011;Honda et al, 2009;Huang, 2009;Park et al, 2010). In parallel with these experiments of tissue engineering, attempts are also made to reconstruct a whole tooth (Arany et al, 2009;Hu et al, 2006a;Komine et al, 2007;Nakao et al, 2007;Ohazama et al, 2004).…”
Section: Introductionmentioning
confidence: 99%